Broadband Traffic Forecasting in the Transport Network - Radojičić, Valentina; Marković, Goran; Janković, Milan; Drašković, Borko (Promet - Traffic&Transportation, 2012)
This paper proposes a modification of traffic forecast model generated by residential and small business (SOHO, Small Office Home Office) users. The model includes forecasted values of different relevant factors and competition on broadband market. It allows forecasting the number of users for various broadband technologies and interaction impact of long-standing technologies as well as the impact of the new technology entrant on the market. All the necessary parameters are evaluated for the Serbian broadband market. The long-term forecasted results of broadband traffic are given. The analyses and evaluations performed are important inputs for the transport network resources planning.